Perancangan Mebel Multifungsi untuk Apartemen Tipe Studio - Ir Samuel Yamin (Intra, 2017)
Studio-type apartments have started many and rampant in various places and people began to demand of them. This type of apartment is about 18 to 20 square meters in size, with only a bedroom and bathroom. This project is about how to make the furniture so that it can meet user needs and efficiency in the apartment room. From there comes this multifunctional furniture, which can meet the user needs such as lying down, sitting and working / gathering